Organizational Impact On Work Discipline Apac Inti Corpora - Wicaksono, Nugroho Adi; Nanda Adhi Purusa; Kusni Ingsih; Mila Sartika (Jurnal Telekomunikasi dan Informatika, 2024)
This study aims to examine the impact of the work environment, organizational culture, and leadership style on employee work discipline at Apac Inti Corpora. A quantitative approach was used, with a questionnaire distributed to 279 employees selected as the sample, calculated using the Slovin formula with a 5% margin of error, from a population of 2,514 employees. The sampling technique applied was random sampling to ensure that the selection process was random and representative of the entire population. The collected data was analyzed using SPSS 25 software to examine the relationship between the three independent variables and one dependent variable. The leadership style variable specifically assesses staff perspectives on their supervisor's leadership style. The results of the study show that the work environment does not have a significant positive impact on work discipline. However, organizational culture and leadership style were found to have a significant positive effect on employee work discipline. Specifically, these findings indicate that a conducive work environment, supportive organizational culture, and effective leadership style can enhance employees' work discipline in performing their roles and responsibilities.